Incomplete Exchange Rate Pass-Through and Simple Monetary Policy Rules - Malin Adolfson (Sveriges Riksbank, 2002)
This paper investigates the performance of various monetary rules in an open economy with incomplete exchange rate pass-through. Implementing monetary policy through an exchange rate augmented policy rule does not improve social welfare compared to using an optimized Taylor rule, irrespective of the degree of pass-through. A direct exchange rate response improves welfare only if the other reaction coefficients, on inflation and output, are sub-optimal. However, an indirect exchange rate response, through a policy reaction to Consumer Price Index (CPI) inflation rather than to domestic inflation, is welfare enhancing. This result is independent of whether society values domestic or CPI inflation stabilization.
Keywords: E52; E58; F41; 330; Exchange rate pass-through; monetary policy; simple policy rules; small open economy; Taylor rule